Opioid prescribing patterns among otolaryngologists: Crucial insights among the medicare population. (15th February 2018) - Svider, Peter F.; Arianpour, Khashayar; Guo, Eric; Folbe, Elana; Zuliani, Giancarlo; Lin, Hosheng; Eloy, Jean Anderson; Folbe, Adam J.
Abstract : Objectives/Hypothesis: There has been growing recognition of the roles prescription drug misuse and diversion play in facilitating the ongoing opioid epidemic. Our objective was to evaluate opioid prescription patterns among practicing otolaryngologists. Study Design: Retrospective review of a CMS database. Methods: Medicare Part D beneficiary data (2015) were accessed for a list of otolaryngologists. Opioid prescription rates, amount, and supply were calculated. Factors including board certification, experience, gender, and location were obtained for the 9, 068 unique otolaryngologists represented in this dataset. Results: In 2015, otolaryngologists wrote 133, 779 opioid prescriptions for 922, 806 days (6.9 days/per prescription). The majority was for hydrocodone‐acetaminophen (64.0%). Most otolaryngologists (51.2%) prescribed ≤ 10 opioids; 6.1% offered > 50 opioid prescriptions. Men wrote more prescriptions on average. Opioid prescription rates were greatest in the Midwest (4.6%) and least in the Northeast (1.8%), and the highest/lowest rates were in Delaware (8.6%) and New York (1.3%). Midcareer (11 –20 years) otolaryngologists were most likely to write >50 prescriptions. The opioid prescription rate declined with greater experience. Conclusions: Opioid prescriptions written by otolaryngologists may play a significant role in the availability of these agents, as otolaryngologists wrote nearly 1 million days worth of opioids to Medicare beneficiaries in 2015. Although the majority of otolaryngologists write fewer than 11 prescriptions annually, those writing more prescriptions also write lengthier courses. There is significant geographic variation in prescribing patterns, highlighting a lack of consensus, and midcareer otolaryngologists are more aggressive in offering opioids. These findings highlight an urgent need for strengthening educational resources aimed at minimizing unnecessary prescriptions. Level of Evidence: NA. Laryngoscope, 128:1576–1581, 2018